2020
DOI: 10.3390/ijerph17114093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 6 Weeks of Traditional Resistance Training or High Intensity Interval Resistance Training on Body Composition, Aerobic Power and Strength in Healthy Young Subjects: A Randomized Parallel Trial

Abstract: Consistent practice of physical activity has well known positive effects on general health; however, time for exercise remains one major barrier for many. An acute bout of high intensity interval resistance training (HIIRT) increases acute resting energy expenditure (REE) and decreases respiratory ratio (RR), suggesting its potential role on weight loss and increased fatty acid oxidation. The aim of this study was to test the long-term effect of HIIRT on body composition, lipid profile and muscle strength usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 51 publications
3
23
1
8
Order By: Relevance
“…In the present study, significant increases in upper arm, thigh, and chest circumferences were found for all RT groups when comparing pre-, mid-, and post-intervention outcomes over the 10-week RT program applied. This positive change over time in these anthropometric estimations of muscle size is an expected result as a 10-week RT program should be sufficiently long to induce hypertrophic effects in the untrained [19,[29][30][31]. Seynnes et al (2006) observed that changes in muscle size were already detectable after three weeks of RT in recreationally active young healthy males [19].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In the present study, significant increases in upper arm, thigh, and chest circumferences were found for all RT groups when comparing pre-, mid-, and post-intervention outcomes over the 10-week RT program applied. This positive change over time in these anthropometric estimations of muscle size is an expected result as a 10-week RT program should be sufficiently long to induce hypertrophic effects in the untrained [19,[29][30][31]. Seynnes et al (2006) observed that changes in muscle size were already detectable after three weeks of RT in recreationally active young healthy males [19].…”
Section: Discussionmentioning
confidence: 63%
“…Seynnes et al (2006) observed that changes in muscle size were already detectable after three weeks of RT in recreationally active young healthy males [19]. Interestingly, in the study of Moro et al (2020) hypertrophic effects were only observed in recreationally active men who engaged in 8 weeks of high intensity interval RT but not in their peers performing traditional RT [31]. Muscular adaptation and the role of fitness level, training volume, intensity, and periodization are indeed topics that can further be explored [32].…”
Section: Discussionmentioning
confidence: 97%
“…However, unlike these dietary approaches, exercise interventions, such as high-intensity interval training (HIIT) or resistance training (RT), are known to bring beneficial changes in body function and composition, which imply the combination with exercise may counteract this negative effect. It is now well established from various studies that HIIT or RT improve physical function (e.g., ameliorate insulin resistance [24,25], reduce liver fat accumulation [26,27], decrease cardiovascular disease risk [28,29], improve aerobic capacity [30,31], enhance muscle strength [32], and increase LM and FFM [21,30,33,34] [21 (RCT), 30 (RCT), 33 (RCT), 34 (RCT)]. The benefits of HIIT and RT on LM and FFM are attributed to increased energy expenditure due to muscle contraction, which enhances adipose metabolism in muscle tissue and muscle growth-related factor gene expression [35].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of exercise on ALT and AST are less clear in healthy adults. While both aerobic and resistance exercise can decrease ALT in patients with nonalcoholic fatty liver disease [ 10 ], a study by Moro et al [ 11 ] found no change in ALT or AST in healthy young adults following interventions involving high-intensity interval resistance training or resistance training. Furthermore, a study by Skrypnik et al [ 12 ] found that the combination of resistance and endurance training was more effective than endurance training alone in improving liver function in females with abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%